Determinants of the utilisation of sexual and reproductive healthcare services by male adolescents in the Tshwane Metropolitan Municipality in South Africa - Omari Shabani; Takalani G. Tshitangano (AOSIS, 2019)
Background: Male adolescent sexual and reproductive health is one of the essential healthcare programmes in the world. However, male adolescents still face numerous challenges in this area. Determinants of the utilisation of these services need to be known to develop strategies to improve utilisation of the available services by male adolescents. Aim: The aim of this study was to identify the determinants of the utilisation of sexual and reproductive healthcare services by male adolescents in the Tshwane Metropolitan Municipality in South Africa. Setting: The study was conducted in the Tshwane Metropolitan Municipality in South Africa. Methods: An explorative, descriptive and qualitative approach was employed. The study was contextual in nature, and purposive sampling was used. The population of the study consisted of male adolescents (aged 18-24 years) living in the Tshwane metropolitan Municipality. Twenty male adolescents participated in the study. Data collected using semistructured individual interviews were analysed using Tesch's method of data analysis, and measures to ensure trustworthiness and ethical consideration pertaining to the study were established. Results: The perception of existing services was found to be a significant individual factor influencing them negatively in utilising the services. This was linked to the violation of their rights as human beings by healthcare providers, their unmet expressed needs and the ineffectiveness as well as inefficiency of the support structures. Conclusion: These results suggest that utilisation of these services by male adolescents can be improved by changing their perception of the existing services through support from different structures of the society.